2018
DOI: 10.1186/s11671-018-2628-9
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular Magnetic Anisotropy and Hydrogenation-Induced Magnetic Change of Ta/Pd/CoFeMnSi/MgO/Pd Multilayers

Abstract: The perpendicular magnetic anisotropy (PMA) has been achieved in Ta/Pd/CoFeMnSi (CFMS)/MgO/Pd film, in which the Heusler compound CoFeMnSi is one of the most promising candidates for spin gapless semiconductor (SGS). The strong PMA, with the effective anisotropy constant Keff of 5.6 × 105 erg/cm3 (5.6 × 104 J/m3), can be observed in the Ta/Pd/CFMS (2.3 nm)/MgO (1.3 nm)/Pd films annealed at 300 °C. In addition, it was found that the magnetic properties of Ta/Pd/CFMS/MgO/Pd films are sensitive to hydrogen (H2) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Recently, strong PMA has been achieved in Ta/Pd/CoFeMnSi/MgO/Pd multilayers experimentally by You et al , where the Heusler alloy CoFeMnSi is one of the most promising SGS candidates. However, strong SOC (Pd layer) plays an important role in the realization of PMA in Ta/Pd/CoFeMnSi/MgO/Pd multilayers. , So far, there are few reports on the PMA of ferromagnet/oxide heterostructures based on the SGSs with weak SOC. It is necessary to carry out related studies to enrich the development of SGS materials and provide theoretical support for designing SGS-based spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, strong PMA has been achieved in Ta/Pd/CoFeMnSi/MgO/Pd multilayers experimentally by You et al , where the Heusler alloy CoFeMnSi is one of the most promising SGS candidates. However, strong SOC (Pd layer) plays an important role in the realization of PMA in Ta/Pd/CoFeMnSi/MgO/Pd multilayers. , So far, there are few reports on the PMA of ferromagnet/oxide heterostructures based on the SGSs with weak SOC. It is necessary to carry out related studies to enrich the development of SGS materials and provide theoretical support for designing SGS-based spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Until now, lots of ferromagnet/oxide interface structures with magnetic anisotropy have been investigated using theory and experiments, particularly for the MgO-based interface structures. [9][10][11][12][13] For example, Ikeda et al found that the interfacial PMA between CoFeB and MgO films reaches up to 1.3 mJ m À2 . 11 The tunneling magnetoresistance (TMR) effect is another important characteristic of MRAM devices.…”
Section: Introductionmentioning
confidence: 99%
“…However, the remarkable characteristics of spin gapless semiconductors have to be realized in thin films for spintronics applications . So far, there are only a few Heusler alloys grown in thin-film form with SGS characteristics, which have been reported, e.g., Mn 2 CoAl, CoFeCrAl, Ti 2 MnAl, and CoFeMnSi. Here, we have addressed the growth of the high-quality thin film of yet another alloy, V 2 NiAl, possessing SGS behavior, followed by its detailed structural, magnetic, and transport properties. Due to the unique band structure, devices based on zero-spin-gap half-metal having SGS characteristics with full spin polarization could result in innovative physical properties, unique phenomena, and latest ultramodern technological applications, such as new generation or upgraded spintronic device applications.…”
Section: Introductionmentioning
confidence: 99%